2020
DOI: 10.1007/s42399-020-00496-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Shock Caused by SARS-CoV-2 in a Patient with Serial Negative Nucleic Acid Amplification Tests. Case Report

Abstract: Myocarditis is an unusual manifestation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It has been associated with increased severity of disease and mortality. The diagnosis of coronavirus disease 2019 (COVID-19) is based on positivity of nucleic acid amplification tests (NAAT) of respiratory samples. We report the case of a patient with cardiogenic shock caused by SARS-CoV-2 myocarditis with serial negative upper and lower respiratory nucleic acid amplification tests. Diagnosis was made by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… 134 The exact incidence of CS in these patients is unknown, but observations of cardiogenic and mixed shock in patients with COVID are accumulating in patients both with and without AMI. 135–138 The median duration between onset of symptoms and admission to ICU in critically ill COVID-19 patients has been 9–10 days, suggesting a gradual respiratory deterioration in most patients. 139 A simple, actionable classification scheme for CS diagnosis has recently been proposed.…”
Section: Diagnosis Of Cardiovascular Conditions In Covid-19 Patientsmentioning
confidence: 99%
“… 134 The exact incidence of CS in these patients is unknown, but observations of cardiogenic and mixed shock in patients with COVID are accumulating in patients both with and without AMI. 135–138 The median duration between onset of symptoms and admission to ICU in critically ill COVID-19 patients has been 9–10 days, suggesting a gradual respiratory deterioration in most patients. 139 A simple, actionable classification scheme for CS diagnosis has recently been proposed.…”
Section: Diagnosis Of Cardiovascular Conditions In Covid-19 Patientsmentioning
confidence: 99%
“…A total of 221 patients with MIS-A were identified: 102 were from the CDC’s MIS-C surveillance system, of whom 55 were described in a recent publication 3 ; 20 were from voluntary reports to the CDC, of whom 9 were included in a recent publication 2 ; and 99 were from case reports published in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…In total, 449 relevant articles were identified, and 86 were selected for in-depth review; of these, 60 had data for patients with MIS-A. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Figure 1 summarizes...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One out of every five hospitalized COVID-19 patients suffering from cardiac injury reflects an accumulation of troponin (a cardiac muscle-specific marker) in blood and the same happens with those having pre-existing heart ailments. Also, for this kind of myocardial injury in-hospital mortality, troponin accumulation is an indicator of morbidity risk (19). Moreover, it has been observed that patients with higher troponin amounts also have increased levels of many inflammatory markers [including interleukin-6(IL-6), C-reactive protein, ferritin, lactate dehydrogenase (LDH), and an increased neutrophil count] and heart dysfunction (amino-terminal pro-B-type natriuretic peptide) (20).…”
Section: Covid-19 and Its Systemic Implicationsmentioning
confidence: 99%